Hidrolise de nucleotideos da adenina em pacientes com meningite asseptica e bacteriana - Dorneles, Aracélli Gnatta (2007)
The meningitis is a serious inflammatory illness of meninges, the membranes that recover and protect encephalo and the spinal cord. The main causing agents of the meningitis are the viruses and the bacteria. Some works affirm that the adenosine, the final product of ATP hydrolysis (when degraded by ectonucleotidases), have an important protective role in brain disorders. Breakdown of extracellular ATP to adenosine is catalyzes by ecto-nucleotidases family, the NTPDase hydrolyze extracellular nucleotide tri and diphosphates (ATP and ADP) to nucleotide monophosphate (AMP) and the 5'-nucleotidase catalyzes the hydrolysis of AMP to adenosine. In this work we verified adenine nucleotides hydrolysis in the CSF of aseptic and bacterial meningitis patients, in order to compare with adenine nucleotides hydrolysis in controls patient (absence of neural inflammatory process). Were used patients with age between 18 and 59 years of both the sex in a sampling of 15 patient controls, 15 patients with aseptic meningitis and 15 patients with bacterial meningitis. For the criteria of inclusion and exclusion had been analyzed parameters like, aspect of the CSF, total counting of leukocytes, distinguishing counting of leukocytes, values of protein, glucose and lactate. We got as resulted a significant reduction of hydrolysis of the ATP in the patients with aseptic and bacterial meningitis when compared with patient controls. In contrast we got a significant increase of hydrolysis of the ADP and the AMP in the two groups of meningitis when compared with the controls. The increase in ADP and AMP hydrolysis maybe means the attempt of increase the adenosine production, that have a recognized neuroprotective actions in brain insults.